Tribo‐electrochemical study of stainless steel surfaces during chemical–mechanical polishing. (3rd February 2016) - Totolin, Vladimir; Göcerler, Hakan; Rodríguez Ripoll, Manel; Jech, Martin
Abstract: Chemical–mechanical polishing combines the synergistic effect of chemical etching and mechanical abrasion to achieve surface planarisation. These effects are discussed in this paper based on a tribocorrosion study of stainless steel (SS) immersed in two different acidic polishing slurries containing iron oxide nanoparticles. The effect of slurry chemistry and contact area on depassivation–repassivation phenomena are investigated and discussed. In case of the point‐contact geometry it was found that high friction and wear caused by formation of third body particles in the contact contributed to slow repassivation time of the SS, and wear accelerated corrosion was the dominant mechanism under these conditions. An increase in the contact area caused a removal of oxides from a larger surface area, leading to much slower repassivation rates and the appearance of a tarnish layer on the SS immersed in a slurry with high acid content. Surface chemistry investigations revealed an enrichment of chromium oxide. Copyright © 2016 John Wiley & Sons, Ltd.